How do we teach clinicians where the resources for best evidence are? (Journal of EAHIL, 2019)
The Sinai Health System (SHS) Library created an online tool kit that groups electronic resources into tiers based on the hierarchy of evidence, in a step-by-step approach. Mobile application options are available for most of the resources. The goal is to provide a simple, practical teaching tool to help clinicians easily find quality health information from the vast offerings of publishers. Since its publication in 2008, the original tool kit received positive feedback from medical students and in-house clinical staff. As well, the tool kit has been incorporated into the teachings of the Royal College of Surgeons and Physicians of Ontario, Ministry of Public Health, and various hospital and patient libraries across the Greater Toronto Area. The SHS Library encourages other libraries and institutions to adapt the tool kit for their users. In the future, this tool kit will be revised to tailor to the research needs of nursing and allied health staff.